2004
DOI: 10.33584/jnzg.2004.66.2569
|View full text |Cite
|
Sign up to set email alerts
|

Grass seed yields increased with plant growth regulators and fungicides

Abstract: Seed yields of ryegrass and tall fescue have increased rapidly over the last seven years; the best farm yields are now reaching 3000 kg/ha, up from 2000 kg/ha. These increases are largely due to the adoption of technologies developed from research funded from grower crop levies and effective technology transfer programmes. The key technologies are (1) the adoption of trinexapac ethyl (TE), a plant growth regulator that blocks gibberellic acid biosynthesis and reduces lodging; and (2) new generation triazole an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Seed yield increased at a maximum rate up to approximately 1.6 l/ha (400 g a.i./ha) followed by a decreasing rate response ( Figure 1) when relative seed yield data (untreated control equals 100%) from ten experiments were combined. These data build on those presented by Rolston et al (2004) where a similar response curve was shown for a single experiment. Increasing Moddus rates generally increased the number of seeds per spikelet at harvest which was directly related to seed yield ( Figure 2).…”
Section: Rate Trialssupporting
confidence: 83%
See 3 more Smart Citations
“…Seed yield increased at a maximum rate up to approximately 1.6 l/ha (400 g a.i./ha) followed by a decreasing rate response ( Figure 1) when relative seed yield data (untreated control equals 100%) from ten experiments were combined. These data build on those presented by Rolston et al (2004) where a similar response curve was shown for a single experiment. Increasing Moddus rates generally increased the number of seeds per spikelet at harvest which was directly related to seed yield ( Figure 2).…”
Section: Rate Trialssupporting
confidence: 83%
“…However grower adoption was limited. The introduction of trinexapac-ethyl (Moddus ® ), a foliar absorbed PGR, revolutionised grass seed yields in New Zealand with average seed yield increases of 50% common (Rolston et al 2004). These results are similar to those achieved by Hebblethwaite et al (1978) who recorded a 40% yield increase when lodging was prevented using wires.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Previously published literature has reported the benefits of strobilurin (azoxystrobin) fungicides in controlling stem rust and increasing seed yield in perennial ryegrass (Rolston et al, 2004; Pfender, 2006), but this information has not been previously available for tall fescue. While there are university recommendations and pesticide labels for the use of strobilurin‐containing fungicides for the control of stem rust in tall fescue, there are no previously published accounts of this fungicide increasing seed yield in tall fescue seed crops (Syngenta Crop Protection, 2013; Anonymous, 2013).…”
Section: Tall Fescue Seed Yield Number Weight and Cleanoutmentioning
confidence: 99%